The Influence Of Learning Style and Students Motivation on Students English Achievement In Higher Education - Marini*, Prameswari Ayudya; Rachman, Dzul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The purpose of this study is to find out the influence of motivation and learning style to students achievement. This study employs a descriptive method using ex-post facto approach and a survey at university. The researcher will conduct 80 participants from 3 classes to answer the questionnaires. The data of motivation were collected by using questionnaire adopted from Gardners Attitude Motivation Test Battery (AMTB) and VARK Questionnaire version 8.0 which was adopted from Flemming to collect the influence of learning style. The studys findings clearly demonstrate that both learning style and motivation significantly influence students academic achievement. Based on the findings, several actionable suggestions can be made for educators, students, and institutions to enhance academic performance.